Identification in culture of a class of hemopoietic colony-forming units with extensive capability to self-renew and generate multipotential hemopoietic colonies. - Nakahata, T (1982)
Mouse marrow and spleen cells formed colonies consisting of 40-1,000 blast cells after 16 days of incubation in methylcellulose culture in the presence of medium conditioned by pokeweed mitogen-stimulated mouse spleen cells. These colonies could be distinguished from other hemopoietic colonies in situ by the complete absence of signs of terminal differentiation. Replating of these colonies (tentatively named stem cell colonies) revealed their self-renewal capacity and the extensive ability to generate secondary colonies, many of which were multipotential hemopoietic colonies. Some of the colonies revealed 100% replating efficiencies. Analyses of individual stem cells colonies revealed concurrent and high incidences of spleen colony-forming units and the macroscopic granulocyte-erythrocyte-macrophage-megakaryocyte colony-forming units (CFU-GEMM) in culture. Replating comparison between the stem cell colonies and GEMM colonies strongly indicated that the progenitors for the stem cell colonies are higher in the hierarchy of stem cell differentiation than are CFU-GEMM. Quantitation of stem cell colonies provides an assay for the class of primitive hemopoietic progenitors described here.